The Molecular Role of HIF1α Is Elucidated in Chronic Myeloid Leukemia - Singh, Vivek; Singh, Ranjana; Kushwaha, Rashmi; Verma, Shailendra Prasad; Tripathi, Anil Kumar; Mahdi, Abbas Ali (Frontiers in Oncology, 2022)
Chronic myeloid leukemia (CML) is potentially fatal blood cancer, but there is an unmet need to discover novel molecular biomarkers. The hypothesis of this study aimed to elucidate the relationship of HIF1α with the redox system, Krebs cycles, notch1, and other regulatory proteins to better understand the pathophysiology and clinical relevance in chronic myeloid leukemia (CML) patients, as the molecular mechanism of this axis is still not clear. This study included CML patient samples (n = 60; 60: blood; 10: bone marrow tissues) and compared them with healthy controls (n = 20; blood). Clinical diagnosis confirmed on bone marrow aspiration, marrow trephine biopsy, and BCR/ABL1 translocation. Cases were subclassified into chronic, accelerated, and blast crises as per WHO guidelines. Molecular experiments included redox parameters, DNA fragmentation, Krebs cycle metabolites, and gene expression by RT-PCR/Western blot/LC-MS, PPI (STRING), Pearson correlation, and ROC curve analysis. Here, our findings show that p210/p190BCR/ABL1 translocation is common in all blast crisis phases of CML. Redox factor/Krebs oncometabolite concentrations were high, leading to upregulation and stabilization of HIF1α. HIF1α leads to the pathogenesis of CML cells by upregulating their downstream genes (Notch 2/4/Ikaros/SIRT1/Foxo-3a/p53, etc.). HIF1α also downregulates ubiquitin proteasomal and apoptotic factors, which can trigger its degradation through proline hydroxylation. However, HIF1α showed an antagonist relation with the notch1 pathway. Notch1 plays a tumor-suppressive role in CML and might have the potential to be used as a diagnostic marker along with other factors in CML patients. The outcome also revealed that oxidant treatment could not be effective in augmentation with conventional therapy because CML cells can enhance the levels of antioxidants for their survival. HIF1α might be a novel therapeutic target other than BCR/ABL1 translocation.